POSSIBILITIES FOR THE DEVELOPMENT OF MEDIUM TOWNS OF MULTIPOLAR SYSTEM OF THE MIDDLE POMERANIA IN THE LIGHT OF ENDOGENOUS AND EXOGENOUS FACTORS (Research Bulletins of the Faculty of Economic Sciences, 2019)
This article indicates that the administrative division of the country is one of the key factors shaping socio-economic ties and should take into account the changing economic potential of regions and the country over the years. The local government reform of 1999 after 20 years has consolidated and deepened the differences in the level of economic development between particular areas of both coastal voivodships. The progressive polarisation of the development of both voivodships within the polarisation-diffusion model was related to the rapid development of the Tri-City metropolis and the Szczecin agglomeration with the progressive sucking of the development potential of their peripheral areas. Middle Pomerania within the framework of territorially balanced development should base its economic development on the five most important urban centres of the potential voivodship of Middle Pomerania. The loss of administrative functions caused a significant weakening of the recorded economic indicators and developmental impulses of Koszalin and Słupsk, while maintaining the rapid growth of the importance of Kołobrzeg as the main centre of the "West Coast" Growth Area. The relatively lower rate of development of service, industrial and communication functions of Koszalin, Słupsk, Szczecinek and Białogard, while maintaining a very rapid development of tourist, spa and service functions in Kołobrzeg, may lead to a change in the importance and significance of individual urban centres over the coming years. When the leading – "export" tourist and health resort functions as well as leisure and recreation functions will become a key factor for the economic development of middle pomerania, the town of Kołobrzeg will have a basis for re-taking the role of the economically most-important town of middle pomerania.
Keywords: multipolar system, functions of towns, FUA, development factors, region